FACTORS ASSOCIATED TO THE ATTENDANCE OF THE ELDERLY AT THE ELDERLY POSYANDU IN THE ORKING AREA UPTD MEURAXA COMMUNITY HEALTH CENTER, BANDA ACEH - Hakim, Alvi Sultani; Amin, Fauzi Ali; Amin, Ghazali; Agustina, Agustina (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Aceh, 2023)
Background: Posyandu for the elderly is an integrated service post for the elderly at the village level within the working area of each Community Health Center (Puskesmas). The active participation of the elderly in Posyandu for the eldery is very important, making it easier for early detection if the eldery suffer from various infectious and non-communicable diseases. The activity of the elderly in the elderly Posyandu in the Meuraxa Health Center was only 29% in 2019, which is still far from the government's target of 70%. This research aims to determine the factors related to the attendance of elderly people at the elderly Posyandu in the working area of the Meuraxa Health Center UPTD, Kota Banda Aceh. Method: This type of research is descriptive- analytic with a cross-sectional approach. The population was 2306 elderly and the sample was 44 elderly (≥ 55 years) obtained through accidental sampling. Data analysis used SPSS with the chi-square test. Results: The research showed that there was a relationship between knowledge (p-value=0.001), education (p-value=0.007), distance from home (p-value=0.012), role of health workers (p-value=0.020), family support (p- value=0.001), the role of cadres (p-value=0.049), and motivation (p-value=0.033) with the presence of elderly people at the elderly Posyandu in the working area of the UPTD Meuraxa Health Center. Recommendation: It is hoped that the head of the Community Health Center will provide more health program guidance and training to health workers and carry out counseling for families with elderly people to increase knowledge, family support, and motivation for elderly to be active in every activity carried out by the elderly Posyandu.